2015
DOI: 10.3329/bjp.v10i4.23039
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin, a dietary flavonoid induces apoptosis via modulating the MAPK and PI3K/Akt signalling pathways in human osteosarcoma (U-2 OS) cells

Abstract: Human osteosarcoma is the most prevalent primary malignant bone tumor with high frequency of invasion and metastasis. Strong resistance coupled with toxicity of the currently available chemotherapeutic drugs poses challenge in treatment. The study aimed to investigate if fisetin, a dietary flavonoid induced apoptosis in human osteosarcoma (U-2 OS) cells. Fisetin at 20-100 µM effectively reduced the viability of OS cells, and induced apoptosis by significantly inducing the expression of caspases (Caspases-3,-8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…These results suggested that P N did affect cell membrane architecture and its integrity could ultimately lead to cell death. Similar results have been obtained with another dietary flavonoid, fisetin, treatment with which resulted in loss of membrane integrity in osteocarcinoma cells [ 53 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results suggested that P N did affect cell membrane architecture and its integrity could ultimately lead to cell death. Similar results have been obtained with another dietary flavonoid, fisetin, treatment with which resulted in loss of membrane integrity in osteocarcinoma cells [ 53 ].…”
Section: Discussionsupporting
confidence: 84%
“…High ROS production in P N -treated cells correlates well with the decreased mitochondrial membrane potential and subsequent increase in apoptosis. Li and his coworkers have also demonstrated an increase in ROS levels by fisetin leading to apoptosis in osteocarcinoma cells [ 53 ]. Similarly, Zhang et al , have demonstrated isoliensinine induced apoptosis in triple-negative human breast cancer cells through ROS generation [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fisetin and other flavonoids have been shown to regulate cell functions, i.e., regulation of vascular smooth muscle contractility [7], protecting against hepatic steatosis [8], also has beneficial effects on anti-neurodegenerative and neuroprotective function [3]. Mechanistically, fisetin could regulate cell function by affecting several important signaling pathways, including PI3K/Akt [9,10], JAK/STAT [11,12], AMPK [8,13], and the Hippo signaling pathway [14]. Furthermore, fisetin can regulate the levels of various growth factors and proinflammatory cytokines, i.e., prostaglandin E2, tumor necrosis factor-alpha (TNF-alpha), interleukin (IL)-1beta, IL-6, and IL-8 depending on the flavonoid structure and the cell types involved [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…These data support the view that the MAPK pathway in H2O2-induced apoptosis is complex. Fisetin, a dietary flavonoid induces apoptosis via modulating the MAPK and PI3K/Akt signalling pathways in human osteosarcoma cells (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%